1998
DOI: 10.1111/j.1749-6632.1998.tb10707.x
|View full text |Cite
|
Sign up to set email alerts
|

Galanin: A Significant Role in Depression?

Abstract: This paper describes a hypothesis that attempts to account for how changes in noradrenergic systems in the brain can affect depression-related behaviors and symptoms. It is hypothesized that increased activity of the locus coeruleus (LC) neurons, the principal norepinephrine (NE)-containing cells in the brain, causes release of galanin (GAL) in the ventral tegmentum (VTA) from LC axon terminals in which GAL is colocalized with NE. It is proposed that GAL release in VTA inhibits the activity of dopaminergic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 64 publications
6
103
0
Order By: Relevance
“…For PAR, the time-course data for adult rats in the present study indicate that this effect develops over treatment time, perhaps determined by gradual changes in brain receptor function and/or other trophic processes triggered by the drug treatment. This decrease in LC activity with AD treatment is consistent with earlier work in our laboratory indicating that symptoms of depression appear in conjunction with disinhibition, and a resultant increase in activity, of LC neurons (for summaries, see Weiss et al , 1996, 1998, 2005). Our earlier research had pointed to the importance of LC activity in depression based on observations that depression-related behavioral changes in rats (a) are accompanied by LC hyperactivity (Simson and Weiss, 1988) and (b) can be prevented by manipulations that counteract LC hyperactivity (Simson et al , 1986).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For PAR, the time-course data for adult rats in the present study indicate that this effect develops over treatment time, perhaps determined by gradual changes in brain receptor function and/or other trophic processes triggered by the drug treatment. This decrease in LC activity with AD treatment is consistent with earlier work in our laboratory indicating that symptoms of depression appear in conjunction with disinhibition, and a resultant increase in activity, of LC neurons (for summaries, see Weiss et al , 1996, 1998, 2005). Our earlier research had pointed to the importance of LC activity in depression based on observations that depression-related behavioral changes in rats (a) are accompanied by LC hyperactivity (Simson and Weiss, 1988) and (b) can be prevented by manipulations that counteract LC hyperactivity (Simson et al , 1986).…”
Section: Discussionsupporting
confidence: 89%
“…We have previously observed that many symptoms of depression appear in conjunction with increase in activity of the principal noradrenergic cell group in the brain, the locus coeruleus (LC) (Simson and Weiss, 1988; Weiss et al , 1996, 1998, 2005). Evidence of LC hyperactivity in depression has been obtained from clinical observations, such as higher cerebrospinal fluid levels of norepinephrine and its primary metabolite 3-methoxy-6-hydroxyphenylglycol (MHPG) in depressives (Ehnvall et al , 2003, Wong et al , 2000) and higher levels of tyrosine hydroxylase, the rate-limiting enzyme for norepinephrine synthesis, in LC of suicide victims (Ordway et al , 1994, Zhu et al , 1999).…”
Section: Introductionmentioning
confidence: 99%
“…administration of galanin (Kuteeva et al, 2007), increased immobility time in the forced swim test (FST) in the rat, indicative of depressionlike behavior. This increase was blocked by the non-specific galanin receptor antagonists M15 and M35, respectively (Weiss et al, 1998;Kuteeva et al, 2007). Moreover, infusion of the galanin antagonist M15 into the VTA, and i.c.v administration of the galanin antagonist M35, reduced immobility, suggesting an antidepressant-like profile of galanin antagonists (Weiss et al, 1998(Weiss et al, , 2005Kuteeva et al, 2007).…”
Section: Introductionmentioning
confidence: 90%
“…A number of behavioral studies suggested a potential role of galanin in depression-like behavior in rodents (see Fuxe et al, 1998;Weiss et al, 1998Weiss et al, , 2005Yoshitake et al, 2004;Kuteeva et al, 2005Kuteeva et al, , 2007Lu et al, 2005aLu et al, , 2007Swanson et al, 2005;Barr et al, 2006;Karlsson and Holmes, 2006;Ö gren et al, 2006). Bilateral infusion of galanin into the ventral tegmental area (VTA) (Weiss et al, 1998), or intracerebroventricular (i.c.v.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation